2019
DOI: 10.5093/pi2019a19
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Key Predictors of Recidivism among Offenders Attending a Batterer Intervention Program: A Survival Analysis

Abstract: Intimate partner violence against women (IPVAW) is a social and public health problem worldwide (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 144 publications
3
55
0
5
Order By: Relevance
“…No significant differences were found between the Spanish batterers and the Latin American immigrant batterers for risk of recidivism. At the end of treatment, a lower risk of recidivism was obtained for both groups (the sum of risk factors and the global risk assessment of both), which is consistent with previous research showing a reduction in the risk of recidivism for BIP completers (Echauri et al, 2013;Lila, Martín-Fernández, Gracia, López-Ossorio & González, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…No significant differences were found between the Spanish batterers and the Latin American immigrant batterers for risk of recidivism. At the end of treatment, a lower risk of recidivism was obtained for both groups (the sum of risk factors and the global risk assessment of both), which is consistent with previous research showing a reduction in the risk of recidivism for BIP completers (Echauri et al, 2013;Lila, Martín-Fernández, Gracia, López-Ossorio & González, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…This body of evidence highlights the importance of incorporating motivational strategies to significantly increase treatment compliance among IPV offenders (Miller & Rollnick, 2002;Musser et al, 2008;Soleymani et al, 2018). These findings have important practical implications, especially considering high dropout rates in IPV offender programs and the link between dropout and higher rates of recidivism reported (Jewell & Wormith, 2010;Lila et al, 2020;Lila et al, 2019;Olver et al, 2011;Stoops et al, 2010). For example, Lila et al (2019) analyzed official recidivism from an IPV offender program and found that dropout was the most predictive variable of official recidivism.…”
Section: 002mentioning
confidence: 99%
“…Several meta-analyses conducted to evaluate the effectiveness of batterer intervention programs (BIPs) have indicated that the effect size of these interventions on reducing recidivism tends to be small (Arce et al, 2020;Babcock et al, 2004;Cheng et al, 2019;Eckhardt et al, 2013;Feder & Wilson, 2005;Smedslund et al, 2011). This limited success of BIPs in reducing recidivism has been attributed to different factors such as low treatment compliance and high dropout rates (Bennett et al, 2007;Daly & Pelowski, 2000;Jewell & Wormith, 2010;Lila et al, 2019;Olver et al, 2011), lack of motivation for change Crane et al, 2015;Eckhardt et al, 2008;Zalmanowitz et al, 2013), problems in building the working alliance (Cadsky et al, 1996;DiGiuseppe et al, 1994;Murphy & Baxter, 1997;Taft et al, 2004), and poor engagement in program activities (Musser et al, 2008;Taft et al, 2003).…”
mentioning
confidence: 99%